The municipal stage of the national reading contest „La izvoarele înțelepciunii” (Confluenţe Bibliologice, 2022)
The article reports about the municipal stage of the literary contest "La izvoarele Întelepcunii",  which was attended by 18 students from Balti gymnasiums and high schools.
Keywords: school library; literary contest